2002
DOI: 10.4315/0362-028x-65.9.1388
|View full text |Cite
|
Sign up to set email alerts
|

Suspending Lettuce Type Influences Recoverability and Radiation Sensitivity of Escherichia coli O157:H7

Abstract: An outbreak strain of Escherichia coli O157:H7 was inoculated onto closely related but structurally distinct types of lettuce (Lactuca sativa): Boston (butterhead lettuce), iceberg (crisphead lettuce), and green leaf and red leaf (colored variants of looseleaf lettuce). The E. coli O157:H7 was inoculated either onto the surface of cut leaf pieces or into a homogenized leaf suspension. Samples were gamma irradiated, and the radiation sensitivity of the inoculated bacteria was expressed as a D-value (the amount … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 20 publications
6
64
1
4
Order By: Relevance
“…[11][12][13] Also, their sensory attributes were not affected by irradiation up to 1 and 2 kGy, respectively. In August 2008, the Food and Drug Administration (FDA) allowed the use of ionizing radiation (up to 3 kGy) to make lettuce and spinach safer and delay spoilage.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…[11][12][13] Also, their sensory attributes were not affected by irradiation up to 1 and 2 kGy, respectively. In August 2008, the Food and Drug Administration (FDA) allowed the use of ionizing radiation (up to 3 kGy) to make lettuce and spinach safer and delay spoilage.…”
mentioning
confidence: 92%
“…Published reports have shown irradiation to be an efficient method for eliminating pathogens from the internal spaces of lettuce and spinach leaf pieces 15) and the D 10 value in the internal regions is three times higher than the value at the surface, 11) which means pathogens in the internal region could be more resistant than the ones on the surface. Even the radiation sensitivity of pathogens appeared to vary with the variety of fresh produce.…”
mentioning
confidence: 99%
“…NIEMIRA et al 20 showed that doses up to 0.5 kGy did not soften lettuce leaves of four varieties (Boston, Iceberg, Green reduced by 1-4 log 10 . Faecal coliforms and Salmonella spp.…”
Section: Microorganismsmentioning
confidence: 99%
“…NIEMIRA et al 20 showed that doses up to 0.5 kGy do not significantly change the texture of four different varieties of lettuce. FOLEY et al 10 and HAGENMAIER and BAKER 13 did not observe any changes in the appearance and texture of iceberg lettuce irradiated at 0.15-0.5 kGy.…”
Section: Introductionmentioning
confidence: 99%
“…However these maximum values depend on the type of products and might modify with new, resistant cultivars (Zhu, et al, 2009). For example, some salad vegetables could resist up to 4000 Gy without physical-chemical damages and considerable quality loss (Nunes et al, 2008) whereas, for some products, such as lettuce leaves and apple fruit (Gala and Fuji variety) radiation doses should not exceed 600 Gy (Dionísio et al, 2009;Niemira et al, 2002).…”
Section: Fruits and Vegetablesmentioning
confidence: 99%